Measuring the Socio-economic Activity of Countries with Social Accounting Matrices - Santos, Susana (2016)
Social Accounting Matrices (SAMs) will be presented as tools that have specific features for studying the socio-economic activity of countries. Such features allow for the reading and interpretation of the reality under study, leading to the production of an empirical work that is not only capable of highlighting specific aspects of that activity, but also offers the chance to experiment with different interventions in regard to its functioning. In stating that the knowledge of the socio-economic activity of countries involves the use of national accounts, emphasis is placed on the desirability of working in a matrix format, which simultaneously includes activities (or industries), products, factors of production and institutions. This will be considered to be a way of capturing the relevant network of linkages and the corresponding multiplier effects in the subsequent modelling of the socio-economic activity of the countries studied. A methodological framework based on the works of R. Stone, G. Pyatt and J. Round, will be adopted outlining the main features of the SAM-based approach, according to which the SAM can describe the activity of countries either empirically or theoretically, depending on whether it is presented in a numerical or an algebraic version, respectively. Based on the latest version of the System of National Accounts (2008 SNA), a proposal for a numerical version of a SAM will be presented. Firstly, a basic structure will be presented and the need to ensure its consistency with the whole system will be emphasized. Such emphasis will then be reinforced through the analysis of possible disaggregations and extensions to that basic structure. The different forms of analysis made possible by the use of aggregates, indicators and balancing items that can be calculated from such a version and which lie outside the matrix format will also be discussed. Finally, that proposal will be compared with the matrix format of the national accounts, proposed by the above referred System of National Accounts. Because any socio-economic study made of a specific space, namely, a country, should involve the consideration of its population, Socio-Demographic Matrices (SDMs) will also be briefly presented and two examples of approaches based on SAMs and SDMs will be sketched out. The exposition will be illustrated with an application to Portugal.